Biological Versus Synthetic Grafts in ACL Reconstruction: A Comparative Analysis of Failure Rates, Knee Stability, and Functional Outcomes - Strašunskas, Karolis; Jurkonis, Rokas (Acta medica Lituanica, 2025)
Background: Anterior cruciate ligament (ACL) injuries are among the most common and impactful musculoskeletal injuries, particularly in athletic populations. A variety of biological and synthetic grafts are used in surgical reconstruction, each offering different biomechanical properties and long-term outcomes. Materials and Methods: This narrative review analyzed 42 original clinical studies published between 1989 and 2024. Articles were retrieved from PubMed and Google Scholar by using terms such as ‘ACL reconstruction’, ‘BPTB’, ‘hamstring tendon’, ‘quadriceps tendon’, ‘LARS’, ‘Leeds-Keio’, and ‘GORE-TEX’. Key outcomes included graft failure rates, postoperative knee stability (e.g., KT-1000, Lachman test), and functional outcomes (Lysholm, Tegner, IKDC). Numerical data were pooled descriptively; no formal meta-analysis was performed. Results: Biological grafts, particularly BPTB and quadriceps tendon autografts, demonstrated the lowest failure rates (as low as 1.2%) and superior mechanical stability (>95% achieving Grade 0–1 laxity) compared to synthetic options. Hamstring tendon autografts were slightly less durable but still reliable. Synthetic grafts, and especially GORE-TEX and Leeds-Keio, were associated with higher failure rates (up to 33%) and complications related to poor biological integration. Conclusions: BPTB and QT autografts remain the most reliable options for ACL reconstruction, offering excellent long-term outcomes. While synthetic grafts may be appropriate in select patients, they carry a higher risk of failure and complications. Graft selection should be individualized based on the patient activity level, anatomical considerations, and tolerance for donor-site morbidity.